2009
DOI: 10.1111/j.1365-3148.2009.00911.x
|View full text |Cite
|
Sign up to set email alerts
|

The EASTR study: a new approach to determine the reasons for transfusion in epidemiological studies

Abstract: Previous studies of blood use have used different methods to obtain and classify transfusion indications. Before undertaking a national study of transfusion recipients, a pilot study was performed over 2 months at two teaching and two district general hospitals to match information from hospital transfusion laboratories with clinical coding data from the hospital's Patients Administration System to determine the indication for transfusion in 2468 recipients. Data analysis revealed major limitations in the conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…This is, however, not the case for the demographic and medical data of the recipient. By linking the databases of the administration of blood products with that of the hospital patient administration system one may obtain information about (broad) patient categories that received defined blood products (Titlestad et al , 2001; Wells et al , 2002; Llewelyn et al , 2009). For this specific question we thought that it might be possible to identify all pregnant women who received blood transfusions.…”
Section: Discussionmentioning
confidence: 99%
“…This is, however, not the case for the demographic and medical data of the recipient. By linking the databases of the administration of blood products with that of the hospital patient administration system one may obtain information about (broad) patient categories that received defined blood products (Titlestad et al , 2001; Wells et al , 2002; Llewelyn et al , 2009). For this specific question we thought that it might be possible to identify all pregnant women who received blood transfusions.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest an increased susceptibility to HBV infection of transplant patients undergoing intensive immunosuppressive therapy in the absence of prophylactic treatment. This situation can be probably derived from organs to blood components as approximately 50% of recipients of blood components in Western Europe present some degree of immunodeficiency [117]. It was shown that both active and passive neutralizing anti-HBs likely delayed but did not prevent acute infection when the immune system was impaired [98].…”
Section: Data Summarized Inmentioning
confidence: 98%
“…Good to excellent coding quality has been demonstrated for the principal procedure and principal diagnosis code (Campbell et al ; Quan et al , ; Henderson et al , ). However, as expected, these individual codes alone do not always reflect the indication for transfusion (Llewelyn et al , ). For example, studies examining indication for RBC transfusion using DRG data identified that patients with high transfusion requirements are often assigned the tracheostomy DRG (Whyte & Brook, ; SyrjĂ€lĂ€ et al , ).…”
mentioning
confidence: 68%
“…For example, studies examining indication for RBC transfusion using DRG data identified that patients with high transfusion requirements are often assigned the tracheostomy DRG (Whyte & Brook, ; SyrjĂ€lĂ€ et al , ). Recent studies using algorithms with combinations of diagnosis codes and the principal procedure code to determine reasons for transfusion are promising (Llewelyn et al , ; Wells et al , ). However, their ability to identify causes of critical bleeding in patients who receive MT is unknown, and previous transfusion validation studies have not been performed in ANZ.…”
mentioning
confidence: 99%